Formation of Research Schools of Higher Educational Establishments: the Second Half of the XIXth – Beginning of the XXth Century - Valentyna Benera (Pedagogical Discourse, 2013)
The article reveals the peculiarities of formation of pedagogical research school in St. Volodymyr University, its efficiency characteristics, inheritance of scientific traditions and key idea of the leader of scientific school. Historic-pedagogical analysis of scientific-pedagogical works of the problem under research is revealed.The analysis of historical-and-pedagogical scientific sourses and archival data on the problem researched is being made. As a result of the research, the definition of the above mentioned didactic category is given. The main characteristic features of students’ individual work in higher educational establishments given by the representatives of progressive pedagogical conception of the period under research are pointed out. The constructive experience of the formation of research schools in higher educational establishments of Ukraine at the given historical period has been actualized.